Architecture [Five cathedrals in Europe ] - Unknown:::Creator:::::::::::: (F.A. Brockhaus; Leipzig; Germany)
Engraving of exterior views of five cathedrals in Europe, including: 1. Münster of Freiburg in Breisgau, 2. Münster in Strasburg, 3. Façade of the cathedral in Köln, 4. St.-Stephanskirche in Vienna, 5. Cathedral in Antwerpen